O REVOZEAMENTO NO DISCURSO DA ESCOLA PÚBLICA CIDADÃ - Conceição, Luciana Etchebest da; Garcez, Pedro de Moraes (Intercâmbio, 2010)
This work describes classroom talk-in-interaction featuring an interactional organization that departs from the traditional triadic initiation/response/feedback sequence. Twenty hours of public school classroom interaction were videorecorded, and selected segments were transcribed for microanalysis. The organization of the segment discussed here is similiar to what has been described as revoicing.